Studi Fenomenologi Tentang Pembelajaran Daring pada Anak Usia Dini dalam Masa Pandemi Covid-19 [Phenomenological Study of Online Learning in Early Childhood Education in the Era of Covid-19 Pandemic] - Mia Febrina Renta Nainggolan (Jurnal Teropong Pendidikan, 2022)
Covid-19 pandemic has had a global impact. One of the steps taken by the Indonesian government as a way to break the chain of the spread of Covid-19 virus is to implement online learning in the education sector. The phenomenon of online learning provides major changes and new habits in the field of education, especially for early childhood education. The purpose of this study is to describe the essence of online learning in early childhood. This research uses a qualitative approach with a phenomenological method to phenomenologically describe online learning. In this phenomenological description, writer describes how online learning is experienced by early childhood and parents. From this research, writer found the essence of the child’s experience regarding the transition to online learning. The results of this study indicate that the transition from offline learning to online learning is a developmental process.